From the Terek region to the Gorskaya ASSR: Terek in 1917-1921 - Lobanov, Vladimir B. (Kavkazologiya, 2022)
The article deals with issues related to the administrative-territorial structure of the Tersk region during the revolution and the Civil War of 1917-1921. This article concluded that various regional regimes have tried to implement their national-territorial projects. However, neither the Gorskо-Cossack Provisional Terek-Dagestan Government, nor the Bolshevik Terek Soviet Republic, nor the liberal-nationalist Mountain Republic, nor the White Guard Terek-Dagestan Region could ad-equately capture the sympathies of the bulk of the local population. The conclusion is given that only the Soviet project related to the creation of the Gorskaya ASSR could attract the mountain peoples of the former Terek region to its side, intercepting the political agenda of the mountain liberal-nationalist political direction, and to ensure a minimum of loyalty to the new government.